Evocação indevida de IG e impedimentos marcário: notas a partir do contencioso CIVC × rosa champagne - Flávio Ribeiro da Costa, Flávio (2025)
Trademarks and geographical indications (GIs) represent forms of registration under industrial property law and share certain similarities, which may at times generate conflicts in the interpretation of their application within the legal framework. This article aims to analyze the conceptual and legal distinction between GIs and trademark registrations granted by the Brazilian Patent and Trademark Office (INPI), highlighting the legal implications arising from possible improper grants. The purpose is to protect product identity and prevent ownership conflicts, through the analysis of a representative case study. For the development of this article, methodological procedures of deductive and qualitative approaches were applied, as well as bibliographic, jurisprudential, and documentary research. As a result, the study seeks to understand the limitations established by the governing legislation, as well as the need to guide the analysis of possible transgressions in light of an apparent conflict between national and international rules. For better comprehension, we present acase study of the Comité Interprofessionnel du Vin de Champagne (CIVC) vs. Rosa Champagne Modas Ltda –ME.